2022
DOI: 10.3389/fmed.2021.528663
|View full text |Cite
|
Sign up to set email alerts
|

Crowned Dens Syndrome: A Case Report and Literature Review

Abstract: Crowned Dens Syndrome (CDS) is the leading cause of acute neck pain and a major cause of reduced neck mobility. The diagnosis of CDS is challenging as clinicians currently have limited awareness of the symptoms of the disease. In this article, we report a case of odontoid syndrome as a reference for the diagnosis and treatment of CDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is clear that CDS can be misdiagnosed as several conditions, including trauma, meningitis, discitis/osteomyelitis, giant cell arteritis, polymyalgia rheumatica, osteomyelitis, fever of unknown origin must be considered and as such an high index of suspicion, for this relatively benign condition is needed. 18 In our case, in particular, the presence of fever, acute cervical pain in an RA patient already taking MTX and NPX raised several diagnostic queries and it was crucial to have the immediate answer through the CT scan that allowed us to avoid steroids and prefer the combination of NPX plus colchicine. This approach led to an almost immediate resolution of fever, and as reported in the literature steroids and NSAIDs may be sometimes unsuccesful.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is clear that CDS can be misdiagnosed as several conditions, including trauma, meningitis, discitis/osteomyelitis, giant cell arteritis, polymyalgia rheumatica, osteomyelitis, fever of unknown origin must be considered and as such an high index of suspicion, for this relatively benign condition is needed. 18 In our case, in particular, the presence of fever, acute cervical pain in an RA patient already taking MTX and NPX raised several diagnostic queries and it was crucial to have the immediate answer through the CT scan that allowed us to avoid steroids and prefer the combination of NPX plus colchicine. This approach led to an almost immediate resolution of fever, and as reported in the literature steroids and NSAIDs may be sometimes unsuccesful.…”
Section: Discussionmentioning
confidence: 83%
“…This approach led to an almost immediate resolution of fever, and as reported in the literature steroids and NSAIDs may be sometimes unsuccesful. 3 19 CDS may be detected in up to 2%–5% of patients over the age of 70 who present to hospital with severe neck pain, 18 20 and since the CDS may cause chronic pain and even spinal cord compression, the diagnosis of simultaneous RA and CDS may represent a really challenging clinical setting. The prompt diagnosis of CDS led us to avoid lumbar puncture and CSF (cerebrospinal fluid) examination.…”
Section: Discussionmentioning
confidence: 99%
“…CDS is currently believed to arise from the deposition of calcium salt crystals in the soft tissue surrounding the odontoid process of the axis vertebra, and these depositions manifest similarly to the ossification of the posterior longitudinal ligament in the cervical spine ( 5 , 9 ). Calcifications surrounding the odontoid process can compress the cervical cord, leading to neurological symptoms of limb weakness.…”
Section: Discussionmentioning
confidence: 99%
“…A notable aspect of this article is that the patient underwent a PET-CT scan to confirm the site of infection, and the PET-CT revealed a hypermetabolic area at the odontoid process level. Previous studies have typically reported CT imaging alone for diagnosis ( 9 , 22 , 23 ). Only Monet has reported PET-CT images of CDS accompanied by polymyalgia rheumatica ( 18 ).…”
Section: Discussionmentioning
confidence: 99%